Prospective Nutraceutical Effects of Cinnamon Derivatives Against Insulin Resistance in Type II Diabetes Mellitus-Evidence From the Literature - Saima Naz Mohsin MS; Faiza Saleem PhD; Ayesha Humayun PhD; Afifa Tanweer PhD; Ambreen Muddassir FCPS (SAGE Publishing, 2023)
Apart from advances in pharmaceutical antidiabetic agents, efforts are being made toward hypoglycemic agents derived from natural sources. Cinnamon has been reported to have significant benefits for human health, particularly as an anti-inflammatory, antidiabetic, and anti-hypertriglyceridemic agent. The phytochemicals in cinnamon can be extracted from different parts of plant by distillation and solvent extraction. These chemicals help in decreasing insulin resistance and can act against hyperglycemia and dyslipidemia, inflammation and oxidative stress, obesity, overweight, and abnormal glycation of proteins. Cinnamon has shown to improve all of these conditions in in vitro , animal, and/or human studies. However, the mechanism of action of active ingredients found in cinnamon remains unclear. The current review presents the outstanding ability of cinnamon derivatives to control diabetes by various pathways modulating insulin release and insulin receptor signaling. It was also found that the type and dosage of cinnamon as well as subject characteristics including drug interactions are likely to affect the response to cinnamon. Future research directions based on this review include the synergistic usage of various cinnamon derivatives in managing and/or preventing diabetes and possible other relevant chronic diseases.